The Impact of Coexistence of Smoking and Diabetes on the Coronary Artery Severity and Outcomes following Percutaneous Coronary Intervention: Results from the 1ST Jordanian PCI Registry - Mohamad I. Jarrah; Said Al-Khatib; Yousef Khader; Hanin N. AlKharabsheh; Ayman Hammoudeh; Karem H. Alzoubi; Nasr Alrabadi (International Journal of Vascular Medicine)
Introduction. Diabetes mellitus (DM) and smoking are highly prevalent among Middle Eastern patients admitted with acute coronary syndrome (ACS) or who undergo percutaneous coronary intervention (PCI). Methods. This study used the analysis of the data from the first Jordanian PCI registry (JoPCR1) to determine the impact of coexistence of smoking and diabetes mellitus on the coronary artery severity and outcome following percutaneous coronary intervention in Middle Eastern patients. Results. Of 2426 patients enrolled, 1300 (53.6%) and 1055 (43.5%) were diabetics and smokers, respectively. The patients’ age was 59.0±10.1 and ranged between 24 and 95 years. Males comprised 79.4% of all patients. The patients were divided into four groups: nondiabetic-nonsmokers (22.2%), diabetic-nonsmokers (34.3%), nondiabetic-smokers (24.2%), and diabetic-smokers (19.2%). Compared with the other three groups, patients in the diabetic-nonsmoker group were older, more likely to be females, and having a higher prevalence of hypertension, dyslipidemia, chronic renal disease, and history of CVD and revascularization. Consequently, the diabetic-nonsmoker patients (but not the diabetic-smokers) had a higher prevalence of multivessel CAD and PCI than the other three groups, highlighting the importance of other risk factors (age, gender, metabolic syndrome, and comorbidities) and not only smoking in predisposing for CAD. Furthermore, those patients had a higher incidence of ACS as an indication for PCI than the stable coronary disease (73% vs 27%) and the highest CRUSADE bleeding risk score (63.9%) among other groups. The in-hospital events including in-stent thrombosis and emergency CABG events did not significantly differ among groups (p=0.5 and 0.22). Heart failure and major bleeding events occurred significantly higher among diabetic-nonsmokers compared to other groups. In-hospital deaths occurred significantly more among diabetic-nonsmokers. Moreover, the one-month and one-year follow-up outcome events (the mortality rate, in-stent thrombosis, readmission for ACS, coronary revascularization, and major bleedings) occurred more frequently in the diabetic-nonsmoker group. However, the difference was statistically significant only for major bleeding incidences. Conclusions. In this analysis of a completed prospective Middle Eastern PCI registry, the majority of the diabetic-nonsmoker (and not the diabetic-smokers) patients (73%) presented with ACS. This group was the highest at risk for in-hospital PCI complications as well as the worst in outcomes after one year of follow-up. Those patients were more likely to be older, female, and have the worst cardiovascular baseline features, highlighting the importance of other risk factors (age, gender, metabolic syndrome, and comorbidities) and not only smoking in predisposing for CAD. Thus, more sufficient education about controlling CVD risk factors should be implemented in the Middle Eastern region.